Effect of PMF Length to Channel Spacing Tunability by Temperature in Multiwavelength Fiber Laser - Sulaiman A.H.; Abdullah F.; Ismail A.; Jamaludin M.Z.; Yusoff N.M.; Mahdi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fiber lasers; Fibers; Optical switches; Polarization-maintaining fiber; Semiconductor optical amplifiers; Temperature distribution; Channel spacings; Intensity-dependent; Lyot filters; Multi wavelength fiber laser; Temperature coefficient; Temperature dependence; Tunabilities; Fiber amplifiers